Just one taste - Edwards, Louisa (Recipe for love novel, 2010)
"Bad-boy chef Wes Murphy is dreading his final-semester cooking class--Food Chemistry 101--until he meets the new substitute teacher. Dr. Rosemary Wilkins is a feast for the eyes, though her approach to food is strictly academic. So Wes decides to rattle her Bunsen burner by asking for her hands-on advice--on aphrodisiacs ..."--P. [4] of cover.